The effect of Al2O3 nanopowder addition on the phase formation and the superconducting properties of Bi1.6Pb0.4Sr1.9Ca2.1Cu3O10-y - A Aftabi; M Mozaffari; P Kameli (Iranian Journal of Physics Research, 2009)
In this work Bi1.6Pb0.4Sr1.9Ca2.1Cu3O10-y superconducting system (Bi2223) has been prepared by solid state reaction and the effect of nanoalumina additive on the phase formation and supercoducting properties have been investigated. XRD investigations show that addition of 0.2 wt% of nanoalumina on the superconducting system improved Bi-2223 phase formation . The results show that Jc increases from 36 A/cm2 for the nanoalumina free sample to 107 A/cm2 for the sample with 0.5 wt% nanoalumina.On the other hand results show that the transition temperature (Tc) of all samples is around 108 K and addition of nanoalumina has not affected Tc significantly .